Synthesis and Antifungal Activity of Aspirin Derivatives - Gao, Sumei; Xu, Zhihong; Wang, Xuesong; Feng, Hui; Wang, Ling; Zhao, Yuanjiang; Wang, Yue; Tang, Xiaorong (Asian Journal of Chemistry, 2014)
Using aspirin as a lead compound, a series of its derivatives (compounds 1-7) were designed and synthesized. Their activity of anti-pathogenic fungi of plants has been evaluated in the laboratory. The results showed that these compounds had good antifungal activity against Sclerotinia sclerotiorum, Helminthosprium maydis, Botrytis cinerea and Rhizoctonia solani. Among them, the inhibition of growth for compounds 1 and 2 against Helminthosprium maydis reached 92.5 and 91.6 % at a concentration of 100 mg L-1, respectively, which was superior to carbendazim.